PENERAPAN ASAS ERGA OMNES DALAM PUTUSAN MAHKAMAH KONSTITUSI NOMOR 30/PUU-XVI/2018 DIKAITKAN DENGAN ASAS NEGATIVE LEGISLATOR - Muchamad Lutfi Hakim; Rasji . (Jurnal Hukum Adigama, 2018)
The problem began because there was an Application to Judicial Review Article 182 Letter l specifically in the phrase "other work" Law Number 7 of 2017. The applicant requested the Constitutional Court to interpret the phrase "other work". The request was finally granted by the Constitutional Court which interpreted the phrase "other work" in Article 182 letter l of the Act to also serve as a Political Party Functionary. For the Decision, there are Parties who disagree, finally the KPU Regulation Number 26 Year 2018 which accommodates the MK Decision so that candidates for DPD members resign from Political Parties to the Administrative Court and MA. The problem is that the Decision of the Administrative Court and Supreme Court is different from the Constitutional Court Decision, both decisions allow political party functionaries to register as candidates for the DPD. In solving these problems the author uses the Normative Legal Research Method, the author's conclusion is that the principle of the Erga Omnes and the principle of the Negative legislator attached to the Constitutional Court Decision is not effective. While the author's suggestion is that there is a need for a revision of the Constitutional Court Law by adding sanctions to institutions or communities that do not follow the MK Decision.